Abnormal intra- and inter-network functional connectivity of brain networks in early-onset Parkinson’s disease and late-onset Parkinson’s disease - Zhou, Fan; Tan, ChangLian; Song, Chendie; Wang, Min; Yuan, Jiaying; Liu, Yujing; Cai, Sainan; Liu, QinRu; Shen, Qin; Tang, Yuqing; Li, Xu; Liao, Haiyan (Frontiers in Aging Neuroscience, 2023)
Objective: The purpose of this study is to look into the altered functional connectivity of brain networks in Early-Onset Parkinson's Disease (EOPD) and Late-Onset Parkinson's Disease (LOPD), as well as their relationship to clinical symptoms. Methods: 50 patients with Parkinson's disease (28 EOPD and 22 LOPD) and 49 healthy controls (25 Young Controls and 24 Old Controls) were admitted to our study. Employing independent component analysis, we constructed the brain networks of EOPD and Young Controls, LOPD and Old Controls respectively, and obtained the functional connectivity alterations in brain networks. Results: Cerebellar network (CN), Sensorimotor Network (SMN), Executive Control Network (ECN) and Default Mode Network (DMN) were selected as networks of interest. Compared with their corresponding health controls, EOPD showed increased functional connectivity in the SMN and ECN and no abnormalities of inter-network functional connectivity were found, LOPD demonstrated increased functional connectivity within the ECN while decreasing functional connectivity within the CN. Furthermore, in LOPD, functional connectivity between the SMN and DMN was increased. The functional connectivity of the postcentral gyrus within the SMN in EOPD was inversely correlated with the Unified Parkinson's Disease Rating Scale Part III scores. Age, age of onset, and MMSE scores are significantly different between EOPD and LOPD (p＜0.05). Conclusions: There is abnormal functional connectivity of networks in EOPD and LOPD, which could be the manifestation of the associated pathological damage or compensation.